(untitled) (KULT_online, 2011)
A November 2008 conference of the German association for ethnography and Berlin’s Institute for European Ethnology at Humboldt University and Museum for European Cultures focused on the influence of (museums-)objects and their culture-generating functions. The central question for researchers was the reforming of contexts, be it in museums or in other arenas of knowledge. The publication presents many of the conference papers which show a cultural-studies point of view of material and medial objects.